(untitled) (Research in Agriculture Livestock and Fisheries, 2025)
This study was conducted to examine fish farming practices within rice-based ecosystems, assess the current status and economic performance of rice-cum-fish culture, and identify key constraints faced by farmers practicing fish culture in rice environments. Primary data on rice–cum–fish farming were collected from fourteen villages across three upazilas of Bagerhat district, Bangladesh, through interviews with 60 randomly selected farmers. Data was analyzed using tabular methods and Microsoft Excel functions. The findings revealed that the per-hectare cost of material inputs for rice–cum–fish culture was Tk 115,590, while the per-hectare cost of human labor was Tk 16,240, resulting in a total production cost of Tk 131,830 per hectare. Average rice yields were 8,648 kg/ha for Boro and 9,882 kg/ha for Aman rice, indicating higher productivity of Aman rice in the study area. In addition, average fish and shrimp production under rice–cum–fish systems were 494.18 ± 40.97 kg/ha and 439.79 ± 30.26 kg/ha, respectively. Major constraints identified by farmers included limited scientific knowledge, unavailability of quality fingerlings, inadequate investment capital, and disease incidence in fish and shrimp. Although training programs provided by government and non-government organizations have contributed to addressing some of these challenges, further efforts are required. The study recommends wider dissemination of improved rice-cum-fish culture techniques and removal of existing constraints to enhance rice and fish productivity as well as farm income. Res. Agric. Livest. Fish. Vol. 12, No. 3, December 2025: 529-546